Politicisation and the Rhetoric of Shanghai Urbanism - Non Arkaraprasertkul (Footprint)
Despite the spectacular contemporary metropolis image of Luijiazui, the new Central Business District (CBD) of Shanghai on the Pudong side of the Huangpu River, this paper discusses the ways Shanghai might be understood through the ‘reality’ of its urbanism. The purpose is to check in a practical way the actuality of the built environment in relation to its history and political presence through first-hand primary sources, which is intended to fill unanticipated voids that surfaced in the understanding of Shanghai in a physical sense. This can be done from the four following perspectives: urban form; individual buildings and urban imagery; visualization of the skylines; and streetscape. Using the city as a primary source, this paper succinctly presents specific information derived from the observations needed to authenticate the research, i.e. to understand the existence of contemporary architecture as a means of urban iconography, which will contribute to the theory of how we conceive and experience the hybridized urban complexity in Asian cities in a practical manner from the perspectives of both the pedestrian and architect-planner critical to the awareness the far-reaching consequence of Shanghai’s urban environment.